2016
DOI: 10.1016/j.ymgmr.2016.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Update on newborn dried bloodspot testing for cerebrotendinous xanthomatosis: An available high-throughput liquid-chromatography tandem mass spectrometry method

Abstract: BackgroundCerebrotendinous xanthomatosis (CTX) is a rare genetic disorder of bile acid synthesis that can cause progressive neurological damage and premature death. Detection of CTX in the newborn period would be beneficial since an effective treatment is available. We previously described a liquid chromatography-electrospray ionization-tandem mass spectrometry (LC-ESI-MS/MS) test with potential to screen newborn dried bloodspots (DBS) for CTX. We report here modifications to the methodology and application of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…Including CTX in universal newborn screening programs could allow early detection and intervention, and in light of the potential benefits of early recognition and treatment, should be added to newborn screening programs when a validated method is available. Rapid isotope-dilution LC-ESI/MS/ MS quantification of the ketosterol bile acid precursor, 7α,12α-dihydroxy-4-cholesten-3-one, in dried bloodspot samples of newborns effectively discriminates between CTX and unaffected newborns, suggesting that 7α,12α-dihydroxy-4-cholesten-3-one may be a useful test marker for screening (Bleyle et al 2016). A recent study evaluating a new dried blood spot screening assay for CTX based on different ratios between the accumulating cholestanetetrol glucuronide (tetrol) and specific bile acids/bile acid intermediates taurochenodeoxycholic acid (t-CDCA) and taurotrihydroxycholestanoic acid (t-THCA), showed that the tetrol:t-CDCA ratio had excellent separation between CTX patients and controls, Zellweger patients, and newborns with cholestasis, suggesting that this derived biomarker has the potential for use in newborn screening programs .…”
Section: Future Researchmentioning
confidence: 99%
“…Including CTX in universal newborn screening programs could allow early detection and intervention, and in light of the potential benefits of early recognition and treatment, should be added to newborn screening programs when a validated method is available. Rapid isotope-dilution LC-ESI/MS/ MS quantification of the ketosterol bile acid precursor, 7α,12α-dihydroxy-4-cholesten-3-one, in dried bloodspot samples of newborns effectively discriminates between CTX and unaffected newborns, suggesting that 7α,12α-dihydroxy-4-cholesten-3-one may be a useful test marker for screening (Bleyle et al 2016). A recent study evaluating a new dried blood spot screening assay for CTX based on different ratios between the accumulating cholestanetetrol glucuronide (tetrol) and specific bile acids/bile acid intermediates taurochenodeoxycholic acid (t-CDCA) and taurotrihydroxycholestanoic acid (t-THCA), showed that the tetrol:t-CDCA ratio had excellent separation between CTX patients and controls, Zellweger patients, and newborns with cholestasis, suggesting that this derived biomarker has the potential for use in newborn screening programs .…”
Section: Future Researchmentioning
confidence: 99%
“…Biochemical approaches to screen newborn dried bloodspots (DBSs) for CTX have recently been described (22)(23)(24). The defect in CTX results in the accumulation of bile acid precursors, including the ketosterols, 7-hydroxy-4-cholesten-3-one and 7,12-dihydroxy-4-cholesten-3-one (712C4).…”
mentioning
confidence: 99%
“…The defect in CTX results in the accumulation of bile acid precursors, including the ketosterols, 7-hydroxy-4-cholesten-3-one and 7,12-dihydroxy-4-cholesten-3-one (712C4). DeBarber and colleagues have demonstrated that elevated 712C4 can be measured in CTX newborn DBSs using LC-MS/MS (22,23). Analysis of this marker can be used to discriminate CTX-positive from CTX-negative newborn DBSs (22,23), although the necessity for LC and the cost of ketosterol derivatization reagent limits the applicability of this methodology as a first-tier test.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The detection of CTX newborn patients, however, is hampered by the absence of a suitable neonatal screening method in dried blood spots (DBSs). DeBarber and coworkers (13,14) have published a candidate, high-throughput, newborn screening method for CTX that is based on the quantification of a ketosterol intermediate in DBSs using an LC-ESI/MS/MS method. A potential disadvantage is that a derivatization step is required before analysis, complicating implementation into existing neonatal screening programs and at higher costs.…”
mentioning
confidence: 99%